Antimalarial Effect of the Total Glycosides of the Medicinal Plant, Ranunculus japonicus - Hae-Soo Yun; Sylvatrie-Danne Dinzouna-Boutamba; Sanghyun Lee; Zin Moon; Dongmi Kwak; Man-Hee Rhee; Dong-Il Chung; Yeonchul Hong; Youn-Kyoung Goo (Pathogens, 2021)
In traditional Chinese medicine, Ranunculus japonicus has been used to treat various diseases, including malaria, and the young stem of R. japonicus is consumed as a food in the Republic of Korea. However, experimental evidence of the antimalarial effect of R. japonicus has not been evaluated. Therefore, the antimalarial activity of the extract of the young stem of R. japonicus was evaluated in vitro using both chloroquine-sensitive (3D7) and chloroquine-resistant (Dd2) strains; in vivo activity was evaluated in Plasmodium berghei-infected mice via oral administration followed by a four-day suppressive test focused on biochemical and hematological parameters. Exposure to extracts of R. japonicus resulted in significant inhibition of both chloroquine-sensitive (3D7) and resistant (Dd2) strains of P. falciparum, with IC50 values of 6.29 ± 2.78 and 5.36 ± 4.93 μg/mL, respectively. Administration of R. japonicus also resulted in potent antimalarial activity against P. berghei in infected mice with no associated toxicity; treatment also resulted in improved hepatic, renal, and hematologic parameters. These results demonstrate the antimalarial effects of R. japonicus both in vitro and in vivo with no apparent toxicity.